Constructing the nation: literary representations of Indonesian nationalism in Pramoedya Ananta Toer’s works - Putriyatul Jamilah (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Literary representations of nationalism in postcolonial Indonesia shape historical consciousness and collective identity. Objective: This study examines how nationalism is constructed in the novels of Pramoedya Ananta Toer, focusing on colonial–indigenous relations and identity formation. Method: A qualitative interpretive approach integrates Critical Discourse Analysis, narrative analysis, and postcolonial criticism of the Buru Quartet. Results: Nationalism is constructed through resistance to colonial knowledge, positioning indigenous subjects as active agents, while narratives depict a shift from individual awareness to collective political identity and function as counter-archives to colonial historiography. Implication: These findings affirm literature’s role in reshaping historical narratives and postcolonial identity discourse. Novelty: This study offers an integrative framework linking discourse, narrative, and historiography to reveal nationalism as both a linguistic and narrative construct.